PENGEMBANGAN USAHA PEMBESARAN KEPITING BAKAU (Scylla spp) MELALUI SISTEM SILVOFISHERY - Siti Saidah; Leila Ariyani Sofia (Jurnal Hutan Tropis, 2016)
Mangrove forest is a forest area on the coast. the type of fragile system that is very sensitive to environmental changes. Exploitation of mangrove forest resources uncontrolled will reduce the quality and quantity of these ecosystems. The purpose of this activity is IbM 1) providing knowledge and skills to the group of fish farmers about enlargement mudcrab with silvofishery system; 2) utilize the mangrove forest resources optimally and sustainably; and 3) increase value added and employment opportunities for coastal communities. Method activities include: 1) dissemination and demonstration; 2) monitoring and evaluation include early stage, middle and end of the program. The analysis shows a change in attitude and knowledge of the group of fish farmers who are less aware to be pretty much know about the cultivation of mangrove crab with the media cage. Enlargement of mud crabs in cages through silvofishery system can restrict the opening of mangrove forests. Besides these efforts provide opportunities for people, not just catch crabs from nature, but also the business of enlarging crab that can improve the quality of the crab be worth selling at high prices.Ekosistem hutan mangrove merupakan kawasan hutan di wilayah pantai.  dengan tipe sistem fragile yang sangat peka terhadap perubahan lingkungan. Eksplotasi sumberdaya hutan mangrove yang tidak terkendali akan menurunkan kualitas dan kuantitas ekosistem tersebut. Tujuan kegiatan IbM ini adalah 1) memberikan pengetahuan dan keterampilan kepada kelompok pembudidaya ikan tentang pembesaran kepiting bakau dengan sistem silvofishery; 2) memanfaatkan sumberdaya hutan mangrove secara optimal dan lestari; dan 3) meningkatkan nilai tambah dan peluang kerja bagi masyarakat pesisir. Metode kegiatan meliputi: 1) sosialisasi dan demonstrasi; 2) pemantauan dan evaluasi meliputi tahap awal, pertengahan dan akhir pelaksanaan program. Hasil analisis menunjukkan adanya perubahan sikap dan pengetahuan kelompok pembudidaya ikan dari yang kurang mengetahui menjadi cukup banyak mengetahui tentang budidaya kepiting bakau dengan media keramba.  Pembesaran kepiting bakau dalam keramba melalui sistem silvofishery dapat membatasi pembukaan hutan mangrove.  Selain itu usaha ini memberikan peluang usaha bagi masyarakat, tidak hanya menangkap  kepiting dari alam, tetapi juga usaha pembesaran kepiting yang mampu meningkatkan kualitas kepiting menjadi layak jual dengan harga tinggi.